(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Advancements in machine learning have propelled innovation across various domains, yet the widespread use of large datasets raises significant concerns regarding individual data privacy. This research paper delves into the intricate landscape of "Data Privacy in Machine Learning," elucidating the challenges and potential solutions in preserving the confidentiality of personal information.